Monocyte-to-Lymphocyte Ratio in the Diagnosis of Lymphoma in Adult Patients - Kamiya N (International Journal of General Medicine, 2022)
Naoko Kamiya,1 Yukiko Ishikawa,1 Kazuhiko Kotani,2 Shuji Hatakeyama,1,3 Masami Matsumura1 1Division of General Internal Medicine, Jichi Medical University Hospital, Shimotsuke-shi, Tochigi, Japan; 2Division of Community and Family Medicine, Center for Community Medicine, Jichi Medical University, Shimotsuke-shi, Tochigi, Japan; 3Division of Infectious Diseases, Jichi Medical University Hospital, Shimotsuke-shi, Tochigi, JapanCorrespondence: Naoko Kamiya, Division of General Internal Medicine, Jichi Medical University Hospital, 3311-1 Yakushiji, Shimotsuke-shi, Tochigi, 329-0498, Japan, Tel +81-285-58-7498, Fax +81-285-40-5160, Email m01015no@jichi.ac.jpBackground: Lymphomas, including Hodgkin lymphoma and non-Hodgkin lymphoma, are one of the differentials for peripheral lymphadenopathy and are difficult to diagnose clinically. Biopsy is essential for diagnosing lymphoma, although it is invasive. Non-invasive methods are required to identify patients with suspected lymphoma who should undergo a biopsy. The relevance of the monocyte-to-lymphocyte ratio has recently been reported to be a useful diagnostic marker in children with lymphoma and a prognostic marker of various other diseases. This study aimed to determine the relevance of the monocyte-to-lymphocyte ratio in the diagnosis of lymphoma in adults.Methods: The study included 246 adult outpatients (median age of 49.0 years) presenting with peripheral lymphadenopathy. The final diagnosis was determined by reviewing the medical records. We categorized all patients into either the lymphoma group or the non-lymphoma group. The lymphoma group included patients who underwent biopsy and were diagnosed with lymphoma by histopathology, while the non-lymphoma group included those diagnosed with disease excluding lymphoma. The monocyte-to-lymphocyte ratios were compared between the two groups.Results: Of the participants, 33 (13.4%) were assigned to the lymphoma group. The median age of the lymphoma and non-lymphoma groups were 67.0 years (interquartile range [IQR] 55.5– 75.5 years) and 46.0 years (IQR 36.0– 61.0 years), respectively. The lymphocyte and monocyte levels showed no significant differences between the two groups individually. Nonetheless, the monocyte-to-lymphocyte ratio was significantly higher in the lymphoma group (median, 0.36; IQR, 0.24– 0.73) than in the non-lymphoma group (median, 0.29; IQR, 0.21– 0.43; P = 0.022), independent of lymph node diameter ≥ 1 cm and C-reactive protein levels.Conclusion: This study suggests that the monocyte-to-lymphocyte ratio can be a helpful diagnostic marker for lymphoma in adults with peripheral lymphadenopathy when the etiology is unclear even after a medical interview and physical examination.Keywords: lymphadenopathy, lymphoma, monocyte-to-lymphocyte ratio, diagnostic marker